Life and death of stars: An analysis from Islamic and modern astronomy perspectives - Abdul Wahab, R. (2015)
Stars are celestial objects having their own life cycles. Stars are born, grow up, mature and eventually die. This paper is aimed to study the explanations for the life and death of stars according to the Islamic perspective from the Quran and the Hadith (Prophetic Traditions) and its correlation and comparison to the modern astronomy context. As a sacred source, it must be noted that the Quran and the Hadith is accepted as the ultimate source of truth. Contrarily, the exegesis of the verses of Quran (namely tafseer) and explanation the Hadith texts given by Muslim Scholars are dynamic, relative and changeable. The author employs inductive and deductive analysis of the verses of the Quran and the Hadith texts related with the life and death of stars. The results show that the life and death of the stars from Islamic and Modern astronomy has some similarities and differences. Islamic perspective shown that that life and death of stars not only changes on their physical aspects but explained the purpose creation of the stars and its beneficial to human life. However, Modern Astronomy explained more details part of changes on the physical aspect of stars in every stages of their life. Therefore, the verses, the exegesis and the hadith texts from Islamic perspectives were correlated to the modern astronomy context throughout analysis on literal descriptions life and death of the stars.